A novel V1a receptor antagonist blocks vasopressin-induced changes in the CNS response to emotional stimuli: an fMRI study - Lee, Royce J.; Coccaro, Emil F.; Cremers, Henk; McCarron, Rosemary; Lu, Shi-fang; Brownstein, MIchael; Simon, Neal G. (Frontiers in Systems Neuroscience, 2013)
Background: We hypothesized that SRX246, a vasopressin V1a receptor antagonist, blocks the effect of intranasally administered vasopressin on brain processing of angry Ekman faces. An interaction of intranasal and oral drug was predicted in the amygdala. Methods: Twenty-nine healthy male subjects received a baseline fMRI scan while they viewed angry faces and then were randomized to receive oral SRX246 (120 mg PO twice a day) or placebo. After an average of 7 days of treatment, they were given an acute dose of intranasal vasopressin (40 IU) or placebo and underwent a second scan. The primary outcome was BOLD activity in the amygdala in response to angry faces. Secondary analyses were focused on ROIs in a brain regions previously linked to vasopressin signaling. Results: In subjects randomized to oral placebo-intranasal vasopressin, there was a significantly diminished amygdala BOLD response from the baseline to post-drug scan compared with oral placebo-intranasal placebo subjects. RM-ANOVA of the BOLD signal changes in the amygdala revealed a significant oral drug × intranasal drug × session interaction (F(1, 25) = 4.353, p < 0.05). Follow-up tests showed that antagonism of AVPR1a with SRX246 blocked the effect of intranasal vasopressin on the neural response to angry faces. Secondary analyses revealed that SRX246 treatment was associated with significantly attenuated BOLD responses to angry faces in the right temporoparietal junction, precuneus, anterior cingulate, and putamen. Exploratory analyses revealed that the interactive and main effects of intranasal vasopressin and SRX246 were not seen for happy or neutral faces, but were detected for aversive faces (fear + anger) and at a trend level for fear faces. Conclusion: We found confirmatory evidence that SRX246 has effects on the amygdala that counter the effects of intranasal vasopressin. These effects were strongest for angry faces, but may generalize to other emotions with an aversive quality.